The influence of music tempo on mental load and hazard perception of novice drivers. (July 2021) - Miao, Lvqing; Gu, Yunjiao; He, Lichun; Wang, Huarong; Schwebel, David C.; Shen, Yongjiang
Highlights: We explored how music tempo affects two key aspects of novice drivers' cognitive functioning. Fast tempo music impacted on mental load and created diminished cognitive capacity compared to slow tempo music. Poorer hazard perception occurred when novice drivers were exposed to fast tempo music. Listening to slow tempo music didn't increase novice drivers' mental load but benifited to their hazard perception. Novice drivers' hazard perception level was poor, reinforcing hazard perception training recommendations. Abstract: Introduction: Many novice drivers listen to music while driving, but the effect of music-listening on novice driver's safety is uncertain. We explored how music tempo affects two key aspects of novice drivers' cognitive functioning, mental load and hazard perception. Method: In a within-subjects experimental design study, 37 novice drivers completed a hazard perception test in simulated traffic situations under four randomly-ordered conditions: while listening to fast, medium, slow tempo music, and without listening to any music. Mental load was recorded both subjectively and through psychophysiological measures during all conditions. Results: When listening to fast-tempo music, novice drivers' subjective load value, heart rate and respiratory rate were significantly higher than that during the other two music tempo conditions and the no music condition. Skin temperature was significantly higher during fast-tempo music than during the slow music tempo and no music conditions. When listening to slow-tempo music, drivers' R-R interval (variability in heart rate, with longer intervals reflecting lower mental load) was significantly longer than while listening to fast and mid-tempo music, and their hazard perception scores were significantly higher than the other three conditions. Conclusions: Listening to fast tempo music was associated with increased mental load and reduced hazard perception ability in traffic among novice drivers. Listening to slow tempo music did not increase novice drivers' mental load and offered some benefit to their hazard perception.